2018
DOI: 10.1242/dmm.034520
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary additives on intestinal permeability in both Drosophila and a human cell co-culture

Abstract: Increased intestinal barrier permeability has been correlated with aging and disease, including type 2 diabetes, Crohn's disease, celiac disease, multiple sclerosis and irritable bowel syndrome. The prevalence of these ailments has risen together with an increase in industrial food processing and food additive consumption. Additives, including sugar, metal oxide nanoparticles, surfactants and sodium chloride, have all been suggested to increase intestinal permeability. We used two complementary model systems t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 139 publications
(201 reference statements)
3
19
0
1
Order By: Relevance
“…E. coli is primarily present in the colon; however, the distal ileum has been shown to contain more Gram-negative than Gram-positive bacteria (5). Our previous work demonstrated increased intestinal permeability in the in vitro Caco-2/HT29-MTX model, and a reduced gut size in Drosophila melanogaster model in response to a high sugar diet, which was rectified with L. rhamnosus (15). Similarly, in this study we found that intestinal permeability was significantly reduced upon exposure to L. rhamnosus ( Figure 5A) and E. coli (Figure 3A) under HG conditions.…”
Section: Discussionmentioning
confidence: 93%
“…E. coli is primarily present in the colon; however, the distal ileum has been shown to contain more Gram-negative than Gram-positive bacteria (5). Our previous work demonstrated increased intestinal permeability in the in vitro Caco-2/HT29-MTX model, and a reduced gut size in Drosophila melanogaster model in response to a high sugar diet, which was rectified with L. rhamnosus (15). Similarly, in this study we found that intestinal permeability was significantly reduced upon exposure to L. rhamnosus ( Figure 5A) and E. coli (Figure 3A) under HG conditions.…”
Section: Discussionmentioning
confidence: 93%
“…Intestinal barrier disruption in flies is known to impact survival 54 . Thus, we examined whether the reduced survival of irradiated flies was due to damage to intestinal tissue.…”
Section: Ionizing Radiation Disrupts Intestinal Integrity and Inducesmentioning
confidence: 99%
“…Cell cultures were incubated at 37°C in a humidi ed atmosphere with 5 % CO 2 and 95 % air. In vitro experiments, the CFs and CMs were cultured with LPS (100 ng/mL) [20] and different concentrations of glucose: 5.5 mmol/L glucose (control) and 30 mmol/L glucose (HG) [21]for 72 h at 37°C with 5% CO 2 , respectively.…”
Section: Methodsmentioning
confidence: 99%